2020
DOI: 10.1016/j.clnu.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver in hereditary fructose intolerance

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is characterized by fat accumulation affecting >5% of the liver volume that is not explained by alcohol abuse. It is known that fructose gives rise to NAFLD and it has been recently described that the ingestion of fructose in low amounts in aldolase B deficient mice is associated with the development of fatty liver. Therefore, it is reasonable that patients with HFI (Hereditary Fructose Intolerance) present fatty liver at diagnosis, but its prevalence in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Another altered pathway affected by F1P accumulation is fatty acid metabolism. Elevated F1P and subsequent activation of adenosine monophosphate (AMP) deaminase followed by inhibition of AMP-activated kinase (AMPK) leads to reduced β-oxidation of fatty acids and accumulation of triglycerides in the liver [ 28 , 29 ]. Furthermore, F1P also impacts glycosylation since it is a competitive inhibitor of liver MPI, which is critical for the N-glycosylation pathway [ 30 ].…”
Section: Fructose Metabolism Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another altered pathway affected by F1P accumulation is fatty acid metabolism. Elevated F1P and subsequent activation of adenosine monophosphate (AMP) deaminase followed by inhibition of AMP-activated kinase (AMPK) leads to reduced β-oxidation of fatty acids and accumulation of triglycerides in the liver [ 28 , 29 ]. Furthermore, F1P also impacts glycosylation since it is a competitive inhibitor of liver MPI, which is critical for the N-glycosylation pathway [ 30 ].…”
Section: Fructose Metabolism Disordersmentioning
confidence: 99%
“…Both hepatic and renal function are affected by ALDOB deficiency. Because of increased accumulation of triglycerides in the liver, HFI patients show a higher prevalence of fatty liver not linked to obesity or insulin resistance [ 29 ]. Pertaining to kidney function, rapid ATP consumption by renal cells to mitigate the lack of downstream metabolites produced by ALDOB leads to depletion of inorganic phosphate and ATP [ 25 , 42 ].…”
Section: Fructose Metabolism Disordersmentioning
confidence: 99%
“…There is a growing use of fructose, as it is widely used as a food additive, and small amounts of this sugar are hidden in many foods. Thus, it is not surprising that HFI patients develop previously unreported complications, such as liver steatosis [7,9] or signs of proximal tubular dysfunction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, 93.8% had sonographic signs of liver steatosis at the end of follow-up. Recently it was suggested that non-alcoholic fatty liver disease (NAFLD) unrelated to obesity is highly prevalent in HFI patients [13]. Previously, Odievre et al considered steatosis as a side effect of long-term strict avoidance of fructose due to an unbalanced diet containing an excess of fat [14].…”
Section: Discussionmentioning
confidence: 99%